Pembuatan Wadah Baterai LiFePO4 Dimensi 410x110x315 mm, 3,7 V, 250 mA, Kapasitas 0,69 Unit/Jam - Devyna Lufhf Imtiyaaz; Syamsul Hadi; Dharma Indi; Muhammad Fauzan Hidayah; Daman Huri Abas; Auliya Kadzi (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2026)
LiFePO4 battery energy storage in the form of a container to drive an electric motorbike that requires 72 V and 11A for a distance of 42 km, and an average speed of 30 km/h as a problem faced in the field. The purpose of making a battery container is to be able to store 3.7 V, 250 mA energy with dimensions of 410 mm in length, 110 mm in width, 315 mm in height that can withstand a weight of 10.3 kg, a duration of 16 hours. The manufacturing method includes: preparation of 3 tensile test specimens and 3 flexural test specimens; tensile testing and flexural testing; design of a series of battery cell containers assembled with completeness of both hand grips; preparation of 3D printing ABS filament material; printing several containers, several clamps and several bolts with 3D printing; assembly with 3D printed clamps; stiffness and strength testing; and quality-dimensional inspection. The result of the manufacture is a LiFePO4 battery container with dimensions of 410 mm in length, 110 mm in width, 315 mm in height from ABS 3D printing, production costs of IDR 544,000.00/unit and a process duration of 87 minutes/unit, with a weight of 10.3 kg which means that the LiFePO4 battery container with dimensions of 410x110x315 mm, and specifications of 3.7, V 250 mA can be used well for certain types of electric motorbikes.